Morquio Disease : A Case Report - Chowdhury, Pranab Kumar; Chowdhury, Dhiman; Karim, Mohammed Rezaul; Gosh, Sankar Kumar (Journal of Chittagong Medical College Teachers’ Association, 2014)
Mucopolysaccharidoses (MPS) are hereditary progressive metabolic disorder caused by the absence or malfunctioning of lysosomal enzyme needed to breakdown molecule called glycosaminoglycan (GAGS) [1]. The major GAGS are chondrotin 4 sulfate, heparin sulfate, dermaten sulfate and hyaluranan. People with mucopolysacaride disease either do not produce enough one of the enzyme required to break down these sugar chain into simple molecule or they produce enzyme that don't work [2]. Morquio disease (MPS IV) is caused by a deficiency of Nacetylgalactosamine-6-sulfatase (MPS IV-A) or of B-galactosidase (MPS IV-B). Both result in the defective degradation of keratan sulfate [2,3]. The incidence of MPS is between 3.5 to 4.5/100000. The most common subtype is MPS III. Our case is a 8 month old son of a non-consanguineous parents from Sandwip, Chittagong, admitted to the Department of Paediatrics, Chittagong Medical College Hospital with a history of gibbus at thoracolumber region for last two months. But on examination he was found to be macrochphalic, stunted and wasted. Skeletal survey had shown some consistent findings of Morquio disease and his urine for Mucopolysaccharidoses screening test is also positive. We have reported this case of MPS as it is rarer and among the MPS, Morquio disease is also not a commoner one [4,5). It is also necessary for early differentiation of MPS IV from some treatable clinical entity like congenital hypothroidism. JCMCTA 2013 ; 24 (2): 48-50